Pengaruh Pijat Bayi terhadap Kualitas Tidur pada Balita Stunting - Respati Prawestri; Dwi Astuti; Nor Asiyah (Midwifery Care Journal, 2026)
Stunting represents a pathological condition characterized by impaired growth and developmental progression, primarily attributed to chronic malnutrition, which is frequently aggravated by suboptimal sleep quality. Given that approximately 75% of growth hormone secretion occurs during sleep, the attainment of adequate sleep quality is paramount for toddlers experiencing stunting. Infant massage constitutes a form of tactile therapy designed to enhance the quality of sleep. The objective of this investigation was to assess the impact of infant massage on sleep quality among stunted toddlers at the Dawe Community Health Center located in Kudus Regency. Employing a quasi-experimental design featuring a one-group pre-post-test framework, a cohort of 40 stunted toddlers aged between 2 to 5 years was recruited through purposive sampling techniques. The intervention involved administering infant massage sessions once weekly over a duration of three weeks. Data analysis was conducted utilizing the Wilcoxon Signed-Rank test. The findings revealed a p-value of 0.000 (< 0.05), signifying a statistically significant effect of infant massage on sleep quality. In summary, the implementation of regular infant massage has been demonstrated to substantially enhance the sleep quality of stunted toddlers. It is recommended that this practice be adopted as a health promotion strategy for parents to facilitate their children's growth and developmental processes